Management составляющая Tools of Organizational words Culture of Modern основные Enterprises ("Journal "U". Economy. Management. Finance.", 2017)
The article  придает describes the  способствует impact of corporate  культуры culture on management  inst effectiveness, the main  управления mechanisms of its  составляющая formation, and  долгосрочной identifies diagnostic  этапе methods and management   определяется managemtnmm   manatools of  цof oforganizational  участие culture of modern  человеческие enterprises.
Keywords: corporate values; behavior patterns; organizational culture; personnel; human resources